EXTRACTION AND IMMOBILIZATION OF LIPASE FROM AVOCADO (Persea americana Mill.) AND COCONUT (Cocos nucifera L.) SEEDS USING NA-ALGINATE - Khairunnisa; Helmi; Zaki Ihsan; Diah Miftahul Aini (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2026)
Enzymes are widely used in industry due to their function as efficient natural catalysts, especially lipase. Avocado (Persea americana Mill.) and coconut (Cocos nucifera L.) seeds are potential sources of lipase. Along with the increasing use of enzymes, enzyme immobilization methods are being developed to improve enzyme stability and activity. Na-alginate is a polymer formed from D-mannuronic acid and L-guluronic acid, which is known to increase enzyme resistance to temperature and pH, reduce inhibition, and maintain enzyme stability. The purpose of this study was the extraction of lipase from avocado and coconut seeds and lipase immobilization with Na-Alginate. The methods used in this study were lipase extraction from avocado and coconut seeds, lipase activity test, and lipase immobilization with Na-alginate. The results showed that lipase had been successfully extracted from avocado and coconut seeds. The activity test showed that the activity of the crude lipase extract in avocado seeds (0.870 mg/mL) was higher than that in coconut (0.626 mg/mL). The success of the lipase immobilization process with Na-alginate was demonstrated by the presence of stable granules dropped into CuCl2 and FeCl2 solutions. This research identified an environmentally friendly source of lipase, necessitating further development for industrial applications.   ABSTRAK Enzim digunakan secara luas dalam industri karena fungsinya sebagai katalisator alami yang efisien, terutama lipase. Biji alpukat (Persea americana Mill.) dan kelapa (Cocos nucifera L.) merupakan sumber potensial penghasil lipase. Seiring dengan semakin luasnya penggunaan enzim, metode imobilisasi enzim sedang dikembangkan untuk meningkatkan stabilitas dan aktivitas enzim. Na-alginat adalah polimer yang terbentuk dari asam D-mannuronat dan L-guluronat yang dikenal dapat meningkatkan ketahanan enzim terhadap suhu dan pH, mengurangi hambatan, serta menjaga kestabilan enzim. Tujuan dari penelitian ini adalah ekstraksi lipase dari biji alpukat dan kelapa serta imobilisasi lipase dengan Na-Alginat. Metode yang dilakukan dalam penelitian ini yaitu ekstraksi lipase dari biji alpukat dan kelapa, uji aktivitas lipase, dan imobilisasi lipase dengan Na-alginat. Hasil penelitian menunjukkan bahwa lipase telah berhasil diekstrak dari biji alpukat dan kelapa. Uji aktivitas menunjukkan bahwa aktivitas ekstrak kasar lipase pada biji alpukat (0,870 mg/mL) lebih tinggi dibandingkan kelapa (0,626 mg/mL). Keberhasilan proses imobilisasi lipase dengan Na-alginat ditunjukkan dengan adanya butiran yang stabil yang ditetesi ke dalam larutan CuCl2 dan FeCl2. Penelitian ini menemukan sumber lipase yang ramah lingkungan, sehingga perlu dilakukan pengembangan lebih lanjut untuk aplikasi industri.